Answer:
[tex]-10r^{2} +38r-24[/tex]
Step-by-step explanation:
Apply FOIL method: [tex](a+b)(c+d)=ac+ad+bc+bd[/tex]
[tex]a=2r,b=-6,c=-5r,d=4[/tex]
[tex]=2r(5-r)+2r*4+(-6)(-5r)+(-6)*4[/tex]
Apply minus - plus rules
[tex]+(-a)=-a,(-a)(-b)=ab[/tex]
[tex]=-2*5rr+2*4r+6*5r-6*4[/tex]
Simplify
Multiply [tex]-2*5rr=-10r^{2}[/tex]
[tex]=-10r^{2} +2*4r+6*5r-6*4[/tex]
Multiply [tex]2*4r=8r[/tex]
[tex]=-10r^{2} +8r+6*5r-6*4[/tex]
Multiply [tex]6*5r=30r[/tex]
[tex]=-10r^{2} +8r+30r-6*4[/tex]
Combine like terms
[tex]=-10r^{2} +38r-6*4[/tex]
Multiply [tex]-6*4=-24[/tex]
[tex]=-10r^{2} +38r-24[/tex]
[tex]-10r^{2} +38r-24[/tex]